2004
DOI: 10.1007/s00402-004-0662-9
|View full text |Cite
|
Sign up to set email alerts
|

Morbidity and mortality after hip fracture: the impact of operative delay

Abstract: These findings suggest that early (within 48 h) surgical treatment of hip fractures is associated with improved 1-year survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
1
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(24 citation statements)
references
References 33 publications
3
19
1
1
Order By: Relevance
“…Similar findings were also reported from Casaletto and Gatt [18], Zuckerman et al [19], and Elliott et al [20]. Gdalevich et al [21] reported their results of 651 patients and found early surgery within 48 h was associated with improved 1-year mortality. Since the premorbid status and pre-existing co-morbidities of the patients will also affect mortality, there have been attempts to classify patients as ‘fit for surgery’ and ‘with medical co-morbidities’.…”
Section: Resultssupporting
confidence: 82%
“…Similar findings were also reported from Casaletto and Gatt [18], Zuckerman et al [19], and Elliott et al [20]. Gdalevich et al [21] reported their results of 651 patients and found early surgery within 48 h was associated with improved 1-year mortality. Since the premorbid status and pre-existing co-morbidities of the patients will also affect mortality, there have been attempts to classify patients as ‘fit for surgery’ and ‘with medical co-morbidities’.…”
Section: Resultssupporting
confidence: 82%
“…The mortality rates in our study exceed other estimates previously reported [1]; [7]; [8]; [14]; [28]. This might be due to the non-selected patient population including some patients with multiple co-existing diseases.…”
Section: Discussioncontrasting
confidence: 59%
“…The majority of the patients (87%) in our assessment underwent surgery within 48 hours after admission. Hereby, our patient population differs from most other studies, where the interval of surgical delay was wider [1]; [8]; [12]; [13]; [16]; [28], making them difficult to compare. As an example, patients who in other studies would have been delayed for medical reasons, might have been included in the <48 hours group of our study.…”
Section: Discussionmentioning
confidence: 93%
“…A number of studies have identified early surgical intervention as a significant prognostic factor in outcomes for patients presenting with hip fractures. 25-27 It was not feasible to accurately measure time to medical clearance in this investigation, but we believe that preoperative medical optimization has improved with the OHC, allowing us to expedite operative intervention. Having the patients admitted to the orthopedic floor provides access to physical therapists who routinely work exclusively with orthopedic patients and accelerate discharge planning.…”
Section: Discussionmentioning
confidence: 94%